Original papersRisk is not flat. Comprehensive approach to multidimensional risk management in ST-elevation myocardial infarction treated with primary angioplasty (ANIN STEMI Registry) - Kruk, Mariusz; Przyłuski, Jakub; Kalińczuk, Łukasz; Pręgowski, Jerzy; Kaczmarska, Edyta; Petryka, Joanna; Kępka, Cezary; Bekta, Paweł; Chmielak, Zbigniew; Demkow, Marcin; Ciszewski, Andrzej; Karcz, Maciej; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction: Current risk assessment concepts in ST-elevation myocardial infarction (STEMI) are suboptimal for guiding clinical management. Aim : To elaborate a composite risk management concept for STEMI, enhancing clinical decision making. Material and methods : 1995 unselected, registry patients with STEMI treated with primary percutaneous coronary intervention (pPCI) (mean age 60.1 years, 72.1% men) were included in the study. The independent risk markers were grouped by means of factor analysis, and the appropriate hazards were identified. Results : In-hospital death was the primary outcome, observed in 95 (4.7%) patients. Independent predictors of mortality included age, leukocytosis, hyperglycemia, tachycardia, low blood pressure, impaired renal function, Killip > 1, anemia, and history of coronary disease. The factor analysis identified two significant clusters of risk markers: 1. age-anemia- impaired renal function, interpreted as the patient-related hazard; and 2. tachycardia-Killip > 1-hyperglycemia-leukocytosis, interpreted as the event-related (hemodynamic) hazard. The hazard levels (from low to high) were defined based on the number of respective risk markers. Patient-related hazard determined outcomes most significantly within the low hemodynamic hazard group. Conclusions : The dissection of the global risk into the combination of patient- and event-related (hemodynamic) hazards allows comprehensive assessment and management of several, often contradictory sources of risk in STEMI. The cohort of high-risk STEMI patients despite hemodynamically trivial infarction face the most suboptimal outcomes under the current invasive management strategy.